Inorganic salt phase change material as well as preparation method and application thereof
By using inorganic salt phase change material composition in the heat pump system, the phase change temperature is reduced through the action of hydrogen bonds and polyols, the problems of heat source temperature increase and energy efficiency ratio caused by high phase change temperature are solved, and the heat pump system is realized Improved energy efficiency.
Patent Information
- Application Number
- CN202411369759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
In the heat pump system, the high phase change temperature of the phase change material leads to an increase in the heat source temperature, large heat transfer loss, and low energy efficiency ratio. It is difficult to meet the demand for effluent temperature while improving the heating water efficiency of the heat pump system.
By preparing an inorganic salt phase change material composition, including inorganic hydrated salts, temperature regulators, nucleating agents, co-nucleating agents and thickening agents, the phase change temperature is reduced and the phase change temperature is increased through the dual action of hydrogen bond formation and polyols. Phase change stability, optimize the energy efficiency of the heat pump system.
The phase change temperature of phase change materials is reduced, the heat source temperature requirement is reduced, the heat loss is reduced, the energy efficiency ratio of the heat pump system is improved, and the energy efficiency is improved while meeting the effluent temperature requirements.
Smart Images

Figure CN119264877A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to an inorganic salt phase change material and a preparation method and application thereof. Background Art
[0002] With the deepening of industrialization, the energy gap is becoming more and more obvious. The shortage of primary energy has attracted great attention from people. For this reason, humans have come up with many solutions. Improving energy utilization and developing renewable energy have become important issues.
[0003] Phase change energy storage is a technology that uses phase changes (solid-liquid, gas-liquid) of materials to store energy. The heating process involves two processes: sensible heat storage and latent heat storage. During the latent heat storage process, the material temperature is almost constant. Compared with water that only uses sensible heat to store heat, phase change materials have higher heat storage capacity. Therefore, phase change materials have very high application advantages in heat pump systems. For example, in the temperature range of 10°C to 65°C, the energy storage density of phase change materials is twice that of water, and the volume of the phase change module can be reduced to 50% of that of an independent water tank.
[0004] In the heat pump system, the phase change material absorbs heat from the heat source during its energy storage process, and transfers heat to low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the phase change material, the higher the outlet water temperature. However, at the same time, the required heat source temperature is also higher. The higher the temperature of the heat source, the greater the loss in the heat transfer process, and the lower the energy efficiency ratio (COP) of the heat pump system. Therefore, it is necessary to optimize the heat exchange material of the heat pump system to improve the hot water production energy efficiency of the heat pump system while meeting the outlet water temperature requirements. Summary of the invention
[0005] The embodiments of the present application provide an inorganic salt phase change material and a preparation method and application thereof, which can improve the hot water production efficiency of a heat pump system by lowering the phase change temperature of the phase change material.
[0006] In a first aspect, an embodiment of the present application provides an inorganic salt phase change material composition, the composition comprising the following components:
[0007] Inorganic hydrated salt 80.0wt.%~94.0wt.%, temperature regulator 4.0wt.%~10.0wt.%, nucleating agent 1.0wt.%~5.0wt.%, auxiliary nucleating agent 0.5wt.%~2.0wt.%, thickener 0.5wt.%~3.0wt.%;
[0008] Wherein, the temperature regulator is selected from at least one of polyols.
[0009] In some embodiments, based on the total weight of the composition, the composition comprises the following components:
[0010] Inorganic hydrated salt 90.0 wt.% to 94.0 wt.%, temperature regulator 6.0 wt.% to 8.0 wt.%, nucleating agent 3.0 wt.% to 4.0 wt.%, co-nucleating agent 0.5 wt.% to 1.0 wt.%, thickener 0.8 wt.% to 1.2 wt.%.
[0011] In some embodiments, the weight ratio of the inorganic hydrated salt to the temperature regulator is S, and the range of S is 11.25 to 15.
[0012] In some embodiments, the melting point of the inorganic hydrated salt is Tm;
[0013] When Tm satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, the inorganic hydrated salt is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, potassium acetate monohydrate;
[0014] When Tm satisfies the conditional formula 35°C < Tm ≤ 50°C, the inorganic hydrated salt is selected from at least one of sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, magnesium sulfate pentahydrate.
[0015] In some embodiments, the polyol is selected from at least one of xylitol, mannitol, erythritol, glycerol, sorbitol.
[0016] In some embodiments, the nucleating agent is selected from at least one of sodium salts, strontium salts, metal mineral materials; the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium carbonate, disodium hydrogen phosphate heptahydrate; the strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate, strontium carbonate, strontium nitrate, strontium sulfate; the metal oxide material of the nucleating agent is selected from at least one of alumina, magnesia, zinc oxide, iron oxide.
[0017] In some embodiments, the co-nucleating agent is selected from at least one of non-metal mineral materials, and the non-metal mineral materials are selected from at least one of mica, montmorillonite, quartz, expanded perlite, sepiolite, talc, zircon.
[0018] In some embodiments, the thickener is selected from at least one of sodium polyacrylate, chitosan, xanthan gum, sodium carboxymethyl cellulose, soluble starch, carrageenan.
[0019] In some embodiments, the composition further comprises a thermal conductive filler, and based on the total weight of the composition, the weight percentage content of the thermal conductive filler is 1.5 wt.% to 3.0 wt.%;
[0020] The thermally conductive filler is selected from at least one of foamed copper, foamed nickel, expanded graphite, boron nitride, and molybdenum disulfide.
[0021] In a second aspect, the present application provides a method for preparing an inorganic salt phase change material, comprising: mixing the components in the inorganic salt phase change material composition as described above.
[0022] In some embodiments, mixing the components of the inorganic salt phase change material composition comprises the following steps:
[0023] The inorganic hydrated salt is heated to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt, and a preheating treatment is performed to obtain a molten inorganic hydrated salt;
[0024] Adding the nucleating agent to the molten inorganic hydrated salt and performing emulsification treatment to obtain a mixture A;
[0025] Adding the nucleating agent to the mixture A for premixing to obtain a mixture B;
[0026] Adding a thermally conductive filler to the mixture B and blending the mixture to obtain a mixture C;
[0027] Wherein, the temperature regulator is added in any step of the preheating treatment, the emulsification treatment, the premixing treatment and the blending treatment;
[0028] Adding a thickener to the mixture C for thickening to obtain a mixture D;
[0029] The mixture D is cooled and solidified to form an inorganic salt phase change material.
[0030] In some embodiments, the preheating treatment at least includes: a time of 2 hours to 4 hours, and the preheating temperature is higher than the melting point of the inorganic hydrated salt in the temperature range of 18° C. to 22° C.
[0031] In some embodiments, the emulsification treatment at least includes: a stirring speed of 6000 r / min to 8000 r / min and a time of 0.5 h to 1 h.
[0032] In some embodiments, the premixing process at least includes: a stirring speed of 80 r / min to 120 r / min and a time of 0.5 h to 1 h.
[0033] In some embodiments, the blending process at least includes: a stirring speed of 100 r / min to 150 r / min, an ultrasonic frequency of 30 kHz to 60 kHz, and a time of 0.25 h to 0.5 h.
[0034] In some embodiments, the thickening treatment at least includes: adding the thickener to the blend in batches, with a stirring speed of 20 r / min to 60 r / min, for 2 h to 3 h, and the weight of the thickener added each time is 0.5% to 0.6% of the total weight of the thickener.
[0035] In a third aspect, the present application provides an inorganic salt phase change material, which is prepared by the preparation method as described above.
[0036] In a fourth aspect, the present application provides a heat pump system, comprising a heat storage unit, wherein the heat storage unit comprises:
[0037] A heat storage shell having a heat storage chamber inside;
[0038] a heat exchange tube, passing through the heat storage cavity and having an end extending out of the heat storage shell; and
[0039] As described above, the inorganic salt phase change material is filled in the heat storage cavity and coated on the middle part of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
[0040] Based on the inorganic salt phase change material and its preparation method and application in the embodiments of the present application, by adding a temperature regulator and selecting the content of each component in the inorganic salt phase change material composition to be within an appropriate range, in the system of the inorganic salt phase change material of the present application, the polyol of the temperature regulator can form hydrogen bonds with the inorganic hydrated salt. In addition, the polyol can play a dual role as a solute and a solvent. When the content is 4% to 10%, the inorganic salt phase change material can be solvated, thereby reducing the overall phase change temperature of the inorganic salt phase change material. In addition, in the frequent melt-crystallization phase change process, the inorganic salt phase change material has good phase change stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0042] Figure 1 This is a flow chart of a method for preparing an inorganic salt phase change material according to an embodiment of the present application;
[0043] Figure 2 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application.
[0044] Reference numerals:
[0045] 10. Heat pump system; 20. Phase change layer;
[0046] 100. heat storage unit; 110. heat storage housing;
[0047] 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0048] 300, heat source; 310, outlet end; 320, inlet end; 400, heating unit;
[0049] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0050] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0051] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0052] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0053] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0054] As mentioned above, the present application provides an inorganic salt phase change material composition, which can be used to prepare an inorganic salt phase change material. The inorganic salt phase change material can be used in a heat pump system to store and release heat.
[0055] Specifically, the inorganic salt phase change material absorbs heat from the heat source during its energy storage process, and the inorganic salt phase change material transfers heat to the low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the inorganic salt phase change material, the higher the water outlet temperature. However, at the same time, the required heat source temperature is also higher. The higher the temperature of the heat source, the greater the loss in the heat transfer process, and the lower the energy efficiency ratio (COP) of the heat pump system. For example, when the temperature requirement of the heated domestic water is 40°C to 50°C, the phase change material with a phase change temperature of 58°C or 52°C is used for phase change energy storage, which can meet the temperature requirement of domestic water. When the phase change temperature of the phase change material is 58°C, a heat source of 65°C is required for phase change energy storage. When the phase change temperature of the phase change material is 52°C, only a heat source of 60°C is required for phase change energy storage. The heat loss of a heat source of 65°C is greater than that of a heat source of 60°C. Correspondingly, the energy efficiency ratio of the heat pump system using a heat source of 65°C is lower. Based on this, the present application optimizes the inorganic salt phase change material and reduces the phase change temperature of the inorganic salt phase change material, so that the heat pump system can use a low-temperature heat source, reduce heat loss, and thus improve the energy efficiency ratio of the heat pump system.
[0056] The inorganic salt phase change material composition of the present application embodiment includes the following components:
[0057] 80.0wt.% to 94.0wt.% of inorganic hydrated salt, 4.0wt.% to 10.0wt.% of temperature regulator, 2.0wt.% to 4.0wt.% of nucleating agent, 0.1wt.% to 1.0wt.% of auxiliary nucleating agent, 0.5wt.% to 1.50wt.% of thickener; wherein the temperature regulator is selected from at least one of the polyols.
[0058] In the present application, inorganic hydrated salt is the main component that undergoes phase change in the inorganic salt phase change material. The nucleating agent is used to provide nucleation sites for the inorganic hydrated salt so that the inorganic salt phase change material can be repeatedly melted and crystallized to perform phase change energy storage. The nucleating agent helps to improve the crystal stability and crystal integrity of the inorganic hydrated salt crystal, helps to improve the thermal enthalpy of the phase change material, and enhances the heat storage capacity of the inorganic salt phase change material. The thickener can increase the overall viscosity of the inorganic salt phase change material to inhibit the phase separation of the inorganic salt phase change material, so that the inorganic salt phase change material has good stability during frequent phase changes. The phase change temperature of the inorganic hydrated salt is the basis of the phase change temperature of the inorganic salt phase change material. In the embodiment of the present application, a temperature regulator is added, and the content of each component in the inorganic salt phase change material composition is selected within a suitable range. In the system of the inorganic salt phase change material of the present application, the polyol of the temperature regulator can form hydrogen bonds with the inorganic hydrated salt. In addition, the polyol can act as a dual role of solute and solvent. When the content is 4% to 10%, the inorganic salt phase change material can be solvated, thereby reducing the overall phase change temperature of the inorganic salt phase change material, and in the frequent melting-crystallization phase change process, it has good phase change stability. When the weight percentage of the inorganic hydrated salt is lower than the lower limit of 80.0wt.%, the thermal enthalpy value decreases. When the weight percentage of the inorganic hydrated salt is higher than the upper limit of 94.0wt.%, it is not conducive to inhibiting phase separation. When the weight percentage of the temperature regulator is lower than the lower limit of 4.0wt.%, the polyol content is insufficient to form sufficient hydrogen bonds with the hydrated salt, resulting in an insignificant decrease in the phase change temperature; when the weight percentage of the temperature regulator is higher than the upper limit of 10.0wt.%, there is too much polyol and the degree of solvation of the hydrated salt is high, resulting in the phase change material not crystallizing and reducing the energy storage density.
[0059] In some embodiments, based on the total weight of the composition, the composition includes the following components: 90.0 wt.% to 94.0 wt.% of inorganic hydrated salt, 6.0 wt.% to 8.0 wt.% of temperature regulator, 3.0 wt.% to 4.0 wt.% of nucleating agent, 0.5 wt.% to 1.0 wt.% of auxiliary nucleating agent, and 0.8 wt.% to 1.2 wt.% of thickener. Under this component, the inorganic salt phase change material has better phase change stability, more stable control of water temperature, and can further improve the hot water production energy efficiency of the heat pump system.
[0060] In some embodiments, the weight ratio of the inorganic hydrated salt to the temperature regulator is S, and the range of S is 11.25 to 15, which is convenient for selecting the contents of both the inorganic hydrated salt and the temperature regulator within a suitable range, so that the temperature regulator can reduce the temperature within a suitable range, thereby enabling the inorganic salt phase change material to obtain a suitable phase change temperature. When the weight ratio S of the inorganic hydrated salt to the temperature regulator is less than 11.25, it is difficult for the temperature regulator to achieve the effect of reducing the phase change temperature (temperature regulation) or the temperature reduction effect is poor and it is difficult to reach the target temperature; when the weight ratio S of the inorganic hydrated salt to the temperature regulator is greater than 15, a large number of hydrogen bonds are formed between the hydroxyl groups of the polyol and the crystal water, resulting in difficulty for the crystal water to form crystals with the inorganic salt or no crystallization will occur, resulting in the phase change material showing multi-temperature point phase changes within a certain temperature range (for example, it is possible to have the first phase change at 50 °C and the second phase change at 30 °C), resulting in problems such as poor heat storage capacity or poor stability of the phase change material.
[0061] The melting point Tm of the inorganic hydrated salt is the basis for the phase change temperature of the inorganic salt phase change material. That is, in the embodiments of the present application, by adding a temperature regulator, an inorganic salt phase change material with a reduced phase change temperature based on the melting point of the inorganic hydrated salt is obtained.
[0062] In some embodiments, when Tm satisfies the conditional formula 50 °C ≤ Tm ≤ 65 °C, the inorganic hydrated salt is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, and potassium acetate monohydrate.
[0063] In some embodiments, when Tm satisfies the conditional formula 35 °C < Tm ≤ 50 °C, the inorganic hydrated salt is selected from at least one of sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, and magnesium sulfate pentahydrate.
[0064] In some embodiments, the polyol of the temperature regulator is selected from at least one of xylitol, mannitol, erythritol, glycerol, and sorbitol. By selecting the above polyols, the stability of the phase change temperature of the obtained inorganic hydrated phase change material is better.
[0065] In some embodiments, the nucleating agent is selected from at least one of sodium salts, strontium salts, and metal mineral materials. Among them, the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium carbonate, and disodium hydrogen phosphate heptahydrate; the strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate, strontium carbonate, strontium nitrate, and strontium sulfate; the metal oxide material of the nucleating agent is selected from at least one of magnesium oxide, aluminum oxide, zinc oxide, and iron tetroxide. By selecting the above nucleating agents, crystal nucleation sites can be provided for the inorganic hydrated salt, so that the inorganic salt phase change material can repeatedly melt and crystallize, and the phase change stability is better.
[0066] In some embodiments, the nucleating agent is selected from at least one of non-metallic mineral materials, and the non-metallic mineral material of the nucleating agent is selected from at least one of mica, montmorillonite, quartz, expanded perlite, sepiolite, talc, and zircon. By selecting the above nucleating agent, it exists in the phase change material in the form of a heterogeneous nucleating agent, which can prevent the homogeneous nucleating agent from failing at high temperature, and at the same time, a thin film filled with air is formed on the surface of the phase change material, which can prevent water evaporation and improve thermal insulation performance.
[0067] Among them, when the nucleating agent is selected as insoluble particles, the particle size Dv is selected in the embodiment of the present application. 50 Meet 350μm≤Dv 50 The nucleating agent is ≤500 μm. Within this particle size range, the nucleating agent can be evenly dispersed in the inorganic salt phase change material and can smoothly pass through the tube-fin heat exchanger.
[0068] In some embodiments, the thickener is selected from at least one of sodium polyacrylate, chitosan, xanthan gum, sodium carboxycellulose, soluble starch, and carrageenan. The above thickener has good swelling properties and can improve the viscosity of the inorganic salt phase change material, thereby improving the phase separation of the inorganic salt phase change material during the phase change process.
[0069] In some embodiments, the composition further comprises a thermally conductive filler, and the weight percentage of the thermally conductive filler is 1.5 wt.-3.0 wt.% based on the total weight of the composition. The thermal conductivity of inorganic hydrated salts is relatively poor, and the inorganic salt phase change material is selected to further comprise a thermally conductive filler, which has good thermal conductivity and is used to improve the overall thermal conductivity of the inorganic salt phase change material, so as to improve the heat transfer efficiency of the inorganic salt phase change material.
[0070] The thermal conductive filler is selected from at least one of porous materials (foam copper, foam nickel and expanded graphite) and flaky thermal conductive fillers (hexagonal boron nitride, molybdenum disulfide and flaky graphene). In the embodiment of the present application, the thermal conductive filler is selected from insoluble matter and exists as insoluble particles in the inorganic salt phase change material. The particle size Dv of the thermal conductive filler is 50 Meet 200μm≤Dv 50 ≤400μm. Within this particle size range, the components in the inorganic salt phase change material are evenly dispersed and have good stability, which prevents the local sedimentation of the thermal conductive filler, and the thermal conductive filler can play a more uniform and efficient thermal conductive role.
[0071] The present application also provides a method for preparing an inorganic salt phase change material, comprising mixing the components in the inorganic salt phase change material composition as described above to prepare the inorganic salt phase change material.
[0072] In the embodiment of the present application, mixing the components of the inorganic salt phase change material composition includes the following steps:
[0073] Step S110: Heat the inorganic hydrated salt to a preheating temperature which is higher than the melting point of the inorganic hydrated salt, and perform a preheating treatment to obtain a molten inorganic hydrated salt;
[0074] Step S120: Add a nucleating agent to the molten inorganic hydrated salt and perform an emulsification treatment to obtain mixture A;
[0075] Step S130: Add a co-nucleating agent to mixture A and perform a premixing treatment to obtain mixture B;
[0076] Step S140: Add a heat-conducting filler to mixture B and perform a blending treatment to obtain mixture C;
[0077] Among them, the temperature regulator can be added in any one of the preheating treatment in step S110, the emulsification treatment in step S120, the premixing treatment in step S130, and the blending treatment in step S140.
[0078] Step S150: Add a thickening agent to mixture C and perform a thickening treatment to obtain mixture D;
[0079] Step S160: Cool and solidify mixture D to form an inorganic salt phase change material.
[0080] Among them, in steps S120 to S150, the temperature is maintained at the preheating temperature to keep the inorganic hydrated salt in a molten state so that the inorganic hydrated salt and other components are uniformly dispersed. Of course, in some embodiments of the present application, in step S110, the inorganic salt and deionized water can also be mixed according to the molar ratio of the inorganic salt and deionized water in the inorganic hydrated salt and heated to the preheating temperature for preheating treatment to obtain a molten inorganic hydrated salt.
[0081] In some embodiments, the preheating treatment at least includes: the temperature range where the preheating temperature is higher than the melting point Tm of the inorganic hydrated salt is 18°C to 22°C, and the time is 2h to 4h. Under this preheating condition, the inorganic hydrated salt can be fully and uniformly melted to fully and uniformly contact with other components of the inorganic salt phase change material.
[0082] Among them, when the melting point Tm of the inorganic hydrated salt satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, correspondingly, the preheating temperature is 70°C to 80°C and the time is 2h to 3h; when the melting point Tm of the inorganic hydrated salt satisfies the conditional formula 35°C < Tm ≤ 50°C, correspondingly, the preheating temperature is 55°C to 65°C and the time is 1.5h to 2.5h.
[0083] In some embodiments, the emulsification treatment includes at least: a stirring speed of 6000 r / min to 8000 r / min and a time of 0.5 h to 1 h. Under the emulsification treatment conditions, the nucleating agent particles can be stirred and dispersed into the molten inorganic hydrated salt, so that the crystal phase integrity and dispersibility of the crystals formed by the inorganic hydrated salt during the crystallization process are better.
[0084] In some embodiments, the premixing treatment includes at least: a stirring speed of 80 r / min to 120 r / min and a time of 0.5 h to 1 h. Under the premixing treatment conditions, the nucleating agent can be more evenly dispersed between the inorganic hydrated salt and the nucleating agent, thereby achieving the effect of optimizing the crystal form during the crystallization process of the inorganic hydrated salt.
[0085] In some embodiments, the blending treatment at least includes: a stirring speed of 100 r / min to 150 r / min, an ultrasonic frequency of 30 kHz to 60 kHz, and a time of 0.25 h to 0.5 h. Under the blending treatment conditions, ultrasonic treatment can be used to make the components in the inorganic salt phase change material composition more evenly dispersed, among which the thermal conductive filler is evenly dispersed, which also helps to improve the heat transfer uniformity and thermal conductivity efficiency of the prepared inorganic salt phase change material.
[0086] In some embodiments, when the nucleating agent and the thermal conductive filler are insoluble, the nucleating agent and the thermal conductive filler are pulverized separately and then added to the corresponding mixture in the corresponding processing steps. The particle size Dv of the pulverized nucleating agent is 50 Meet 350μm≤Dv 50 ≤500μm, particle size Dv of thermal conductive filler 50 Meet 200μm≤Dv 50 ≤400 μm, so that the nucleating agent and the thermal conductive filler can be evenly dispersed in the premixed liquid. The pulverization process can be carried out by at least one of a ball mill and a high-speed pulverizer.
[0087] In the embodiment of the present application, the temperature regulator polyol can be added in any step of the preheating treatment, emulsification treatment, premixing treatment and blending treatment. For example, the polyol is mixed with the inorganic hydrated salt in the preheating treatment step and then heated to the preheating temperature; or, the polyol is added to the molten inorganic hydrated salt together with the nucleating agent in the emulsification treatment step; or, the polyol is added to the mixture A together with the nucleating agent in the premixing treatment step; or, the polyol is added to the mixture B together with the thermal conductive filler in the blending treatment step.
[0088] In some embodiments, the thickening treatment at least includes: adding the thickener to the blend in batches, and stirring at a speed of 20 r / min to 60 r / min for 2 hours to 3 hours, and the weight of the thickener added each time is 0.5% to 0.6% of the total weight of the thickener. The thickener is added in small amounts and multiple times to facilitate the swelling of the thickener and to evenly disperse it in the inorganic salt phase change material, so as to better improve the phase separation and prevent the thickener from agglomerating and causing uneven dispersion when a large amount of thickener is added.
[0089] The present application also provides a heat pump system 10, which may include a water heater 100, and the water heater 100 may include an energy storage unit, the energy storage unit includes an energy storage shell 110, a heat exchange tube 200 and a phase change layer 20, and the phase change layer 20 includes the inorganic salt phase change material as described above. The energy storage shell 110 has an energy storage cavity inside, and the heat exchange tube 200 includes an inlet section, a middle section and an outlet section connected in sequence, the middle section is arranged in the energy storage cavity, and the inlet section and the outlet section extend from the energy storage cavity to the energy storage shell 110. The phase change layer 20 is filled in the energy storage cavity and coated on the middle section of the heat exchange tube 200 to exchange heat with the heat exchange medium in the heat exchange tube 200.
[0090] In some embodiments, the number of heat exchange tubes 200 of the energy storage unit is multiple. Figure 2 As shown, there are two heat exchange tubes 200, one of which is a first heat exchange tube 210 and the other is a second heat exchange tube 220. The heat pump system 10 further includes a heat source unit 300, the inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source unit 300, and the outlet section is connected to the inlet end 320 of the heat source unit 300, and the heat source unit 300 exchanges heat with the phase change layer 20 through the heat exchange medium in the first heat exchange tube 210.
[0091] The first heat exchange tube 210 and the second heat exchange tube 220 can be made of stainless steel independently. When the inorganic salt phase change material also includes a corrosion inhibitor, the first heat exchange tube 210 and the second heat exchange tube 220 can also include copper material.
[0092] like Figure 2As shown, when the water heater 100 includes an energy storage unit, the inlet section of the second heat exchange tube 220 of the energy storage unit is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The heat storage unit 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat, and the high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section Heat pipe 220, the inorganic hydrated salt transfers heat to the low-temperature water flow in the second heat exchange tube 220, and the low-temperature water flow absorbs heat and becomes high-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use; in the mixed mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and at the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220, the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and transfers the heat to the low-temperature water flow in the second heat exchange tube 220 at the same time, the low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use.
[0093] The heat pump system 10 also includes a heating unit 400, a reversing valve 500 and connecting pipes connecting the various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source 300, the second end is connected to the heating unit 400, and the third end is connected to the heat exchange pipe 200 of the heat storage unit 100. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source 300 can be connected to at least one of the heating unit 400 and the heat storage unit 100 to provide high-temperature heat exchange medium to the heating unit 400 and the heat storage unit 100 accordingly. The number of heating units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple heating units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple heating units 400, and then the heat source 300 is connected to one or more of the multiple heating units 400.
[0094] The following is a method for preparing an inorganic salt phase change material in combination with an embodiment and a comparative example. It will be understood by those skilled in the art that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following embodiments, unless otherwise specified, all raw materials used are commercially available.
[0095] In each embodiment and comparative example of the present application, the performance test method of the inorganic salt phase change material is as follows:
[0096] 1. Phase change temperature and supercooling test method
[0097] The phase change temperature is measured by the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of the inorganic hydrated salt and stabilized for 30 minutes. Then, it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ).
[0098] Theoretical phase transition temperature (T theory ) and the actual phase transition temperature (T actual ) is the supercooling degree (T sc ).
[0099] 2. Phase change temperature reduction rate
[0100] Phase transition temperature reduction rate = (T1-T2) / T1*100%
[0101] Wherein, T1 is the actual phase transition temperature of the inorganic hydrated salt;
[0102] T2 is the actual phase change temperature of the inorganic salt phase change material.
[0103] 3. Test method for thermal enthalpy decay rate after 2000 cycles
[0104] The initial unit mass enthalpy of the phase change material is measured by DSC equipment.
[0105] The phase change material is loaded into the cycle test device and the melt-crystallization cycle is carried out according to the following steps:
[0106] (1) Initial temperature 0°C, let stand for 5 minutes;
[0107] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0108] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0109] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass thermal enthalpy of the phase change material after 2000 cycles is measured by DSC equipment.
[0110] The calculation formula of the thermal enthalpy decay rate per unit mass is: H% = (1-△H n / △H0)×100%;
[0111] Among them, △H n is the unit mass enthalpy of the phase change material after n cycles, kJ / kg;
[0112] △H0 is the initial unit mass enthalpy of the phase change material, kJ / kg.
[0113] 4. Energy storage density test method
[0114] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0115] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0116] The initial unit mass enthalpy ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0117] The energy storage density △Q is calculated according to the following formula:
[0118] △Q=р s ×(T2-10)×C ps +(р s +р l ) / 2×△H0+р l× (65-T2)×C pl .
[0119] Example 1
[0120] This embodiment provides a method for preparing an inorganic hydrated phase change material, the method comprising the following steps:
[0121] (1) Preheating
[0122] 80 g of inorganic salt sodium acetate trihydrate (CH3COONa·3H2O) and 7.0 g of temperature regulator xylitol were weighed and mixed evenly, and heated to a preheating temperature of 70° C. to obtain a molten mixture including CH3COONa·3H2O and xylitol.
[0123] Based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of CH3COONa·3H2O is 80 wt.%, and the weight percentage of xylitol is 7.0 wt.%.
[0124] (2) Emulsification treatment
[0125] At 65° C., 3.5 g of a nucleating agent, disodium hydrogen phosphate dodecahydrate, was added to a mixture of molten CH 3 COONa·3H 2 O and xylitol, and emulsified in an emulsifying device at a stirring speed of 5500 r / min for 0.5 h to obtain a mixture A.
[0126] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of disodium hydrogen phosphate dodecahydrate is 3.5 wt.%.
[0127] (3) Premixing
[0128] At 65°C, the particle size Dv 50 2.0 g of 350 μm sepiolite as a nucleating agent was added to mixture A, and premixed in a mixing device at a stirring speed of 120 r / min for 0.5 h to obtain mixture B.
[0129] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of sepiolite is 2.0 wt.%.
[0130] (4) Blending
[0131] At 75°C, the particle size Dv 50 6.0 g of thermal conductive filler nano-alumina with a size of 400 μm was added to mixture B, and blended in an ultrasonic device at a stirring speed of 120 r / min, an ultrasonic frequency of 40 kHz, and a time of 2.5 h to obtain mixture C.
[0132] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of nano-aluminum oxide is 6.0 wt.%.
[0133] (5) Thickening treatment
[0134] At 65° C., thickeners sodium polyacrylate and carrageenan were added to mixture C in 5 portions, the weight ratio of sodium polyacrylate to carrageenan was 2:1, and 0.3 g was added each time. The mixture was thickened for 2 h at a stirring speed of 40 r / min to obtain mixture D.
[0135] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of sodium carboxymethyl cellulose is 1.5 wt.%.
[0136] (6) Cooling treatment
[0137] The mixture D is cooled to room temperature 25° C., and the mixture D solidifies to form an inorganic salt phase change material.
[0138] Examples 2 to 6, Examples 9 to 14, and Comparative Examples 1 to 4 are the same as Example 1, except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted as shown in Table 1 in each processing step.
[0139] Example 7 is the same as Example 1 except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted in each processing step as shown in Table 1, and the preheating temperature is selected to be 65°C according to the melting point of the inorganic hydrated salt in steps (1)-(5).
[0140] Example 8 is the same as Example 1 except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted in each processing step as shown in Table 1, and the preheating temperature is selected to be 50°C according to the melting point of the inorganic hydrated salt in steps (1)-(5).
[0141] Example 15 is the same as Example 1 except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted as shown in Table 1 in each processing step.
[0142] Example 16 is the same as Example 1 except that the contents of inorganic hydrated salt, temperature regulator, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted as shown in Table 1 in each processing step.
[0143] The preparation parameters and performance parameters of Examples 1 to 16 and Comparative Examples 1 to 4 are shown in Table 1.
[0144] Table 1
[0145]
[0146]
[0147] (In Table 1, for example: in Example 1, the content of the thickener is 1+0.5, which means that the weight percentage of sodium polyacrylate is 1wt.%, and the weight percentage of carrageenan is 10.5wt.%)
[0148] The performance parameters of the inorganic salt phase change materials obtained in Examples 1 to 16 and Comparative Examples 1 to 4 are shown in Table 1.
[0149] Table 2
[0150]
[0151]
[0152] It can be seen from Examples 1-1 to 1-16 and Comparative Examples 1-1 to 1-4 in Tables 1 and 2 that by adding a temperature regulator to the inorganic salt phase change material composition and selecting the components of the inorganic salt phase change material composition within a suitable range, the phase change temperature of the obtained inorganic salt phase change material can be reduced, and the enthalpy decay rate, supercooling and energy storage density after 2000 cycles are all within a suitable range. The inorganic salt phase change material of the embodiments of the present application can be used in a heat pump system and can improve the energy efficiency ratio of the heat pump system.
[0153] It can be seen from Comparative Example 1-1 to Comparative Example 1-2 that the content of the added temperature regulator is between 4wt.% and 10wt.%, and the phase change temperature reduction rate, enthalpy decay rate after 2000 cycles, supercooling and energy storage density of the obtained inorganic phase change material are all within an appropriate range. When the weight percentage of the temperature regulator is lower than 4wt.%, the content of the temperature regulator is insufficient and the effect of lowering the temperature is limited. When the weight percentage of the temperature regulator is higher than 10wt.%, although the temperature regulator can significantly reduce the phase change temperature, it causes the supercooling of the inorganic salt phase change material to deteriorate.
[0154] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An inorganic salt phase change material composition, characterized in that: The composition comprises the following components: Inorganic hydrated salt 80.0 wt.% to 94.0 wt.%, temperature regulator 4.0 wt.% to 10.0 wt.%, nucleating agent 1.0 wt.% to 5.0 wt.%, co-nucleating agent 0.5 wt.% to 2.0 wt.%, thickening agent 0.5 wt.% to 3.0 wt.%; Wherein, the temperature regulator is selected from at least one of polyhydric alcohols.
2. The composition according to claim 1, characterized in that Based on the total weight of the composition, the composition comprises the following components: Inorganic hydrated salt 90.0 wt.% to 94.0 wt.%, temperature regulator 6.0 wt.% to 8.0 wt.%, nucleating agent 3.0 wt.% to 4.0 wt.%, co-nucleating agent 0.5 wt.% to 1.0 wt.%, thickening agent 0.8 wt.% to 1.2 wt.%.
3. The composition according to claim 1 or 2, characterized in that The weight ratio of the inorganic hydrated salt to the temperature regulator is S, and the range of S is 11.25 to 15.
4. The composition according to any one of claims 1, characterized in that The melting point of the inorganic hydrated salt is Tm; When Tm satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, the inorganic hydrated salt is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, potassium acetate monohydrate; When Tm satisfies the conditional formula 35°C < Tm ≤ 50°C, the inorganic hydrated salt is selected from at least one of sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, magnesium sulfate pentahydrate.
5. The composition according to claim 1, characterized in that The polyhydric alcohol is selected from at least one of xylitol, mannitol, erythritol, glycerol, sorbitol.
6. The composition according to claim 1, wherein The nucleating agent is selected from at least one of sodium salts, strontium salts, metal mineral materials; The sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium carbonate, disodium hydrogen phosphate heptahydrate; The strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate, strontium carbonate, strontium nitrate, strontium sulfate; The metal oxide material of the nucleating agent is selected from at least one of alumina, magnesia, zinc oxide, iron oxide; The co-nucleating agent is selected from at least one of non-metal mineral materials, and the non-metal mineral materials are selected from at least one of mica, montmorillonite, quartz, expanded perlite, sepiolite, talc, zircon. The thickening agent is selected from at least one of sodium polyacrylate, chitosan, xanthan gum, sodium carboxymethyl cellulose, soluble starch, carrageenan.
7. The composition according to any one of claims 1 to 6, characterized in that The composition further comprises a thermal conductive filler, and based on the total weight of the composition, the weight percentage content of the thermal conductive filler is 1.5 wt.% to 3.0 wt.%; The thermal conductive filler is selected from at least one of copper foam, nickel foam, expanded graphite, boron nitride, molybdenum disulfide.
8. A method for preparing an inorganic salt phase change material, characterized in that: Comprising: Mixing the components in the inorganic salt phase change material composition according to any one of claims 1-7.
9. The preparation method according to claim 8, characterized in that: Mixing the components of the inorganic salt phase change material composition comprises the following steps: Heating the inorganic hydrated salt to a preheating temperature, the preheating temperature being greater than the melting point of the inorganic hydrated salt, and performing a preheating treatment to obtain a molten inorganic hydrated salt; Adding the nucleating agent to the molten inorganic hydrated salt and performing an emulsification treatment to obtain mixture A; Adding the nucleating agent to the mixture A for premixing to obtain a mixture B; Adding a thermally conductive filler to the mixture B and blending the mixture to obtain a mixture C; Wherein, the temperature regulator is added in any step of the preheating treatment, the emulsification treatment, the premixing treatment and the blending treatment; Adding a thickener to the mixture C for thickening to obtain a mixture D; The mixture D is cooled and solidified to form an inorganic salt phase change material.
10. The composition according to claim 9, characterized in that The preheating treatment at least includes: a time of 2 hours to 4 hours, and the preheating temperature is higher than the melting point of the inorganic hydrated salt in the temperature range of 18°C to 22°C; The emulsification treatment at least includes: stirring at a speed of 6000 r / min to 8000 r / min for 0.5 h to 1 h; The premixing process at least includes: a stirring speed of 80 r / min to 120 r / min and a time of 0.5 h to 1 h; The blending process at least includes: a stirring speed of 100 r / min to 150 r / min, an ultrasonic frequency of 30 kHz to 60 kHz, and a time of 0.25 h to 0.5 h; The thickening treatment at least includes: adding the thickener to the blend in batches, with a stirring speed of 20r / min to 60r / min, for 2h to 3h, and the weight of the thickener added each time is 0.5% to 0.6% of the total weight of the thickener.
11. An inorganic salt phase change material, characterized in that: The inorganic salt phase change material is prepared by the preparation method described in any one of claims 8 to 10.
12. A heat pump system, characterized in that: A heat storage unit is included, wherein the heat storage unit includes: A heat storage shell having a heat storage chamber inside; a heat exchange tube, passing through the heat storage cavity and having an end extending out of the heat storage shell; and The inorganic salt phase change material according to claim 11, wherein the inorganic salt phase change material is filled in the heat storage cavity and coated on the middle part of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
Citation Information
Cited By
Inorganic salt phase change material and preparation method therefor and use thereof
WO2026067090A1